The letter - Evans, Richard Paul. (New York : Simon & Schuster, 1997)
A letter left on his daughter's grave sends a man searching for his mother who abandoned him in childhood. For David Parkins, it's a chance at happiness, his wife having just left him. A sentimental tale set in 1930s Salt Lake City.
"The final book of the Christmas box collection"--Cover.
Accelerated Reader AR
Keywords: Adoptees -- Fiction; Hope -- Fiction; Love stories